Repeatable, Inducible Micro-RNA-Based Technology Tightly Controls Liver Transgene Expression - Iulian I Oprea; Joana R Viola; Pedro M D Moreno; Oscar E Simonson; Sergey Rodin; Nathalie Teller; Karl Tryggvason; Karin E Lundin; Leonard Girnita; Carl Inge Edvard Smith (Elsevier, 2014)
Inducible systems for gene expression emerge as a new class of artificial vectors offering temporal and spatial exogenous control of gene expression. However, most inducible systems are less efficient in vivo and lack the target-organ specificity. In the present study, we have developed and optimized an oligonucleotide-based inducible system for the in vivo control of transgenes in the liver. We generated a set of simple, inducible plasmid-vectors based on the addition of four units of liver-specific miR-122 target sites to the 3'untranslated region of the gene of interest. Once the vector was delivered into hepatocytes this modification induced a dramatic reduction of gene expression that could be restored by the infusion of an antagomir for miR-122. The efficiency of the system was tested in vivo, and displayed low background and strong increase in gene expression upon induction. Moreover, gene expression was repeatedly induced even several months after the first induction showing no toxic effect in vivo. By combining tissue-specific control elements with antagomir treatment we generated, optimized and validated a robust inducible system that could be used successfully for in vivo experimental models requiring tight and cyclic control of gene expression.